Analisis Faktor-Faktor yang memengaruhi Nilai Perusahaan Makanan dan Minuman - William Adam; Satriyo Wibowo (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this research is to analyze the factors that can affect firm value, including profitability, capital structure, liquidity, firm size, and total asset turnover. The objects in this research were taken from food and beverage companies listed on the IDX from 2012-2020. The number of samples in this research were 81 data with 9 companies selected using the purposive sampling method. The data analysis tool used is multiple regression analysis with a significance level of α=5%. The results of this research indicate that profitability has a positive effect on firm value. The higher the profitability, the more efficient and effective the company's performance is, thereby increasing investor interest in investing. Liquidity has a negative effect on firm value. High liquidity does not give a positive signal to investors, thereby reducing investor interest in investing. Meanwhile, capital structure, firm size, and total asset turnover have no effect on firm value.